Celebrate with me! : recipes, crafts, and holiday fun from around the world - Gladwin, Laura; Cardona, Dawn M. (New York : Magic Cat Publishing, 2022)
Celebrate at the tables of artists, designers, and chefs with this book that offers families the chance to share in a world of parties, festivals, and holidays. Each spread features a different holiday and offers a step-by-step recipe, a craft activity, a personal story, and different ways to observe the holiday.
New Year's Day -- Lunar New Year -- Valentine's Day -- Carnival -- International Women's Day -- Holi -- Saint Patrick's Day -- Easter -- Passover -- Songkran -- Mother's Day -- Eid al-Fitr -- Juneteenth -- Summer solstice -- Father's Day -- Mid-autumn festival -- Diwali -- Halloween -- Day of the Dead -- Bonfire Night -- Hanukkah -- Winter solstice -- Christmas -- Kwanzaa -- New Year's Eve -- Birthdays around the world -- More fun with festivals.
Kirkus Review, August 2022
School Library Journal, August 2022
6.7
3-6
Keywords: Handicraft -- Juvenile literature; Holiday cooking -- Juvenile literature; Holidays -- Juvenile literature; Fasts and feasts -- Juvenile literature; Handicraft; Holiday cooking; Holidays; Fasts and feasts; Illustrated works; Recipes; Activity books